A Sensitivity Controllable Thermopile Infrared Sensor by Monolithic Integration of a N-channel Metal Oxide Semiconductor. (27th September 2021) - Li, Hongbo; Xu, Gaobo; Zhang, Chenchen; Mao, Haiyang; Zhou, Na; Chen, Dapeng
Abstract : We report a sensitivity controllable infrared (IR) sensor composed of a thermopile and a n-channel metal oxide semiconductor (NMOS). In the sensor, the cathode of the thermopile is connected with the gate of NMOS. Such a sensor is fabricated by using a CMOS-compatible monolithic integration process. Compared with the separate thermopile IR sensor, sensitivity of the thermopile IR sensor integrated with NMOS can be remarkably enhanced by 357%. In addition, the drain bias voltage of the NMOS can be employed as a quick-response switch. The fabrication process of this device is quite simple and compatible with CMOS processes, thus such a thermopile IR sensor integrated with NMOS is low-cost and suitable for mass production. Moreover, the integration approach can be further applied to develop thermopile arrays for high-resolution imaging.